1996
DOI: 10.1021/jm950664x
|View full text |Cite
|
Sign up to set email alerts
|

Diarylspiro[2.4]heptenes as Orally Active, Highly Selective Cyclooxygenase-2 Inhibitors:  Synthesis and Structure−Activity Relationships

Abstract: A novel series of 5,6-diarylspiro[2.4]hept-5-enes was shown to provide highly potent and selective cyclooxygenase-2 (COX-2) inhibitors. A study of structure-activity relationships in this series suggests that 3,4-disubstituted phenyl analogs are generally more selective than 4-substituted phenyl analogs and that replacement of the methyl sulfone group on the 6-phenyl ring with a sulfonamide moiety results in compounds with superior in vivo pharmacological properties, although with lower COX-2 selectivity. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 24 publications
(75 reference statements)
1
30
0
Order By: Relevance
“…The pharmacophore found in the structure-activityrelationship of selective COX-2 inhibitors appears to be of the general formula aryl methyl sulfonyl and aryl methyl sulfonamide as opposed to the aryl acetic acid and aryl propionic acid found in the non-selective agents [37,38]. This suggests that the binding interaction of COX-2 might be different in its sensitivity to both the electronic and stearic properties of the substitution on the aryl portion.…”
Section: Discussionmentioning
confidence: 95%
“…The pharmacophore found in the structure-activityrelationship of selective COX-2 inhibitors appears to be of the general formula aryl methyl sulfonyl and aryl methyl sulfonamide as opposed to the aryl acetic acid and aryl propionic acid found in the non-selective agents [37,38]. This suggests that the binding interaction of COX-2 might be different in its sensitivity to both the electronic and stearic properties of the substitution on the aryl portion.…”
Section: Discussionmentioning
confidence: 95%
“…The test system was a set of COX-2 inhibitors comprising pyrrole [30], imidazole [31,32], cyclopentene [33,34], benzene [35], pyrazole [36], spiroheptene [37], isoxazole [38], pyridine [39], thiazolone [40], thiadiazole and oxadiazole [41] derivatives. The inhibitory activities of all these molecules were measured on human recombinant enzyme by the same protocol, and are reported as IC 50 values [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory activities of all these molecules were measured on human recombinant enzyme by the same protocol, and are reported as IC 50 values [30][31][32][33][34][35][36][37][38][39][40][41]. The enzyme inhibitory activities were converted to the negative logarithmic scale (pIC 50 ) and as seen in Table 1 spans 5 log orders.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of diarylcarbocycles include four-membered (e.g., cyclobutene and cyclobutenone) [48], five-membered (e.g., cyclopentene and cyclopentenone) [49][50][51], spirocyclic [52,53] and substituted phenyl ring (terphenyl) systems [54,55]. Although preliminary SAR studies suggested that the central ring was essential for favorable spatial orientation of the two pendant phenyl rings, a series of 1,2-and l,l-diarylstilbenes were recently disclosed as potent and selective COX-2 inhibitors [56][57][58].…”
Section: Carbo Cyclesmentioning
confidence: 99%